ANALISIS AKUNTABILITAS DANA DESA DI DESA ALANG-ALANG KECAMATAN MUARA SABAK TIMUR KABUPATEN TANJUNG JABUNG TIMUR TAHUN ANGGARAN 2020-2022 - Tika Andriani; Usdeldi; Achyat Budianto (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
Accountability in accounting is a form of responsibility of the accountant, or report maker for the reports made. Accountability is the basis of financial reporting in government which is based on the public's right to know and receive explanations regarding the collection of resources and their use. This research aims to analyze planning, implementation and accountability for village fund accountability in Alang-Alang Village, Muara Sabak Timur District, East Tanjung Jabung Regency for the 2020-2022 Fiscal Year. The research uses a qualitative approach based on postpositivism philosophy. The object of this research is the accountability of village fund reports based on the 2020-2021 village income and expenditure budget (APBDes). Data collection techniques use interviews, observation and documentation. Based on general research findings, the planning stage for managing village funds carried out by the Alang-Alang Village government has been carried out in an accountable manner because it went through a process starting from deliberation involving the community until it was handed over to the sub-district authorities. Implementation of village funds is carried out by developing a priority scale for villages and communities in the fields of development, community empowerment and humanitarian assistance to the community. Accountability for the implementation of village funds is demonstrated by activity reports and village financial reports. Meanwhile, accountability for the management of village funds is considered to be still not accountable because the Alang-Alang Village government does not print banners so that the public can see the realization of the budget carried out by the Alang-Alang village government.